Pelatihan & Sertifikasi Kompetensi Klaster Servis Sepeda Motor Karburator Untuk Masyarakat Ciwidey Jawa Barat - Adri Maldi Subardjah; Mokhamad Munir Fahmi; Budi Triyono; Dibyo Setiawan; Apri Setiawan; Sulistianto Sunaryo; Jumari; Cahyo Wibowo (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The CSR program is a sustainable commitment ethically, legally, and contributes to improving the quality of life for workers/families, local communities, and society as a whole, such as waste processing, infrastructure development, MSME development, and others. Geo Dipa Energi operates in the field of managing and utilizing geothermal energy for electricity generation. Management is in the Ciwidey area covering 3 villages. The program aims to provide skills, support independence, and open up opportunities to apply for jobs with a skills certificate in the automotive sector. Polban with Public Service Agency status can provide services to the community in the form of providing goods/services in carrying out its activities based on the principles of efficiency and productivity. The method of implementing community service is through financing the Geo Dipa Energi CSR program in collaboration with Polban and LSP TOP. The carburetor motorbike service cluster training and certification includes 22 competency items, 3 batches are implemented, the number of participants is 30, details for each batch consist of 8 days of training, 1 day of simulation, satisfaction survey, registration, online assessment, and 1 day of practical assessment. As a result of the assessment, all participants obtained the title of competent.